Selective Exposure During Uprisings: Examining the Public's News Consumption and Sharing Tendencies During the 2019 Lebanon Protests. (October 2021) - Melki, Jad; Kozman, Claudia
This study examines selective exposure and trust during uprisings. It studies major uses of traditional and social media and assesses the public's trust in these media and their engagement in sharing news. Focusing on the October 2019 Lebanon uprising, the research surveys thousand Lebanese individuals using a nationally representative probability sample. The findings provide support for selective exposure theory beyond the Western context, particularly for people undergoing stressful political change. The findings also provide support to the robustness of issue publics as a theoretical construct that predicts selective exposure to pro-attitudinal news content, as well as support for attitude strength and attitude importance as two separate predictors.